Digital Empowerment of MSMEs: Implications of Digital Loans on Business Sustainability Through Selective Credit Schemes - Ira Murwenie; Erik Kartiko; Alam Avrianto (Jurnal Manajemen dan Kewirausahaan, 2025)
The rapid development of information and communication technology has transformed consumer behavior toward online shopping as part of a modern lifestyle. This study aims to analyze the influence of media exposure, information quality, and digital marketing on online purchase intention, with recipient satisfaction as a mediating variable. The research was conducted on Shopee users in Malang City, representing active online consumers. The population of this study includes all Shopee users in Malang, while the sample was determined using Malhotra’s formula based on the total number of observed indicators, resulting in 105 respondents. Data were collected through a structured questionnaire using a Likert scale and analyzed using path analysis with SPSS to examine direct and indirect effects among variables. The findings show that information quality and digital marketing have a positive and significant effect on recipient satisfaction, whereas media exposure has no significant effect. Furthermore, recipient satisfaction significantly influences online purchase intention and mediates the relationship between information quality, digital marketing, and purchase intention. These results highlight the critical role of satisfaction and information quality in strengthening consumer purchasing behavior in the digital marketplace.